KOMIK DIGITAL B3 ( BUKU BACAAN BERMUTU) SEBAGAI USAHA PENINGKATAN MINAT BACA PESERTA DIDIK PADA SDN SURADADI 03 KECAMATAN SURADADI KABUPATEN TEGAL - Kartika Dewi, Ratna (Cakrawala: Jurnal Pendidikan, 2025)
Abstract Low literacy in Indonesia includes low interest in reading. Of course, interest is defined as a feeling of liking and being interested in something. While reading has many benefits such as increasing brain activity, increasing knowledge, and sharpening memory. The purpose of this study was to determine 1). how is the reading interest of students at SDN Suradadi 03 using digital comics. 2). the effect of using digital comics B3 (Quality Reading Books) in increasing the reading interest of students at SDN Suradadi 03. 3) the effectiveness of student learning achievement by using digital comics B3 (Quality Reading Books) at SDN Suraddai 03. This study uses a Mixed Method research type. In qualitative data using data sources selected from the experimental class using a Multi Stage Random Sampling sampling technique. The data collection technique for this study uses questionnaires, interviews, documentation and tests. While the Data Analysis of this study uses regression analysis and average equality tests. The results of the study showed that B3 digital comics (Quality Reading Books) were proven effective in improving student learning achievement at SDN Suradadi 03, Suradadi District, Tegal Regency. This learning media is designed with an attractive visual approach and content that is in accordance with the learning needs of elementary school students.. Keywords: quality reading books, digital comics, reading interest, learning achievement Komik Digital B3 ( Buku Bacaan Bermutu) Sebagai Usaha Peningkatan Minat Baca Peserta Didik Pada SDN Suradadi 03 Kecamatan Suradadi Kabupaten Tegal